Penerapan Green Supply Chain Management pada Ummi Home Bakery di Kota Palu - Kartika, Kartika; Zainuddin, Fatlina; Syamsuddin, Syamsuddin; Dwiwijaya, Kadek Agus (Jurnal Samudra Ekonomi dan Bisnis, 2025)
The study aims to analyze the implementation of green supply chain management (GSCM) at Ummi Home Bakery, Palu City. This study uses a qualitative approach with data collection methods through observation and interviews. The results of the study indicate the initial implementation of GSCM through collaboration with local suppliers, tote bag use initiatives, and plastic reduction. In addition, product design was identified as not optimal for efficiency, and production was still manual or semi-automatic. Post-consumer packaging constraints also hamper product recycling, but hazardous materials are avoided and expired products are withdrawn. Waste is dumped into rivers or given to farmers with distribution problems. Another problem is that the integration of GSCM criteria in purchasing and supplier selection is still limited, as is environmental cooperation with customers. Internal environmental management is also not formally structured.